Negarawan Sejati Menurut Pandangan Hamka - Faozi, Slamet Faozi; Iqbal, Rahmat; Bagus Baskoro, Rifky Yulian Syah (An Naba, 2021)
The values ​​of struggle that have been exemplified by the nation’s predecessors are costly life lessons. Hamka's capacity as a statesman is very important for his thoughts to appear to the next generation of the country, because Hamka, one of the many national figures owned by Indonesia, is a man known for his strong religious understanding, and is a model of harmony between religion and state. This study uses a qualitative approach that applies a research process to obtain descriptive data results. With this method, it is hoped that the results of this study can provide data and analysis that can represent the theme of the study. Content analysis techniques are used by researchers to draw conclusions that can be imitated or used as a guide by the authors, and the validity of the data by paying attention to its context. Through this technique, the researcher wants to analyze a true statesman according to Hamka as an individual who has a spirit of nationalism and patriotism, which is in accordance with the basic principles of Islam “al-amru bi al-ma’rūf wa an-nahyu ʻan al-munkar”.